2020
DOI: 10.3892/etm.2020.8686
|View full text |Cite
|
Sign up to set email alerts
|

Microarray and bioinformatics analysis of circular RNAs expression profile in traumatic lung injury

Abstract: Acute lung injury (ALI) and respiratory distress syndrome are common, potentially lethal injuries that predominantly occur following chest trauma. Circular RNAs (circRNAs) are stable conserved non-coding RNAs that are widely expressed in different organs. To the best of our knowledge, no previous studies have shown whether circRNAs are involved in traumatic lung injury (TLI). The aim of the present study was to identify highly expressed circRNAs in plasma samples from patients with TLI and explore their potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Mounting studies have shown the evidence that cir-cRNAs can function as miRNA sponge via ceRNA crosstalk in various biologic processes, such as cancer, inflammationrelated, or autoimmune diseases [5,6]. We and other studies have previously documented the differential expressed cir-cRNAs in ARDS mice and constructed circRNA-miRNA interaction networks through using bioinformatic tools [11,23]. However, it is not clear whether those circRNAs can function as ceRNA for the dysregulated miRNAs in ARDS.…”
Section: Discussionmentioning
confidence: 99%
“…Mounting studies have shown the evidence that cir-cRNAs can function as miRNA sponge via ceRNA crosstalk in various biologic processes, such as cancer, inflammationrelated, or autoimmune diseases [5,6]. We and other studies have previously documented the differential expressed cir-cRNAs in ARDS mice and constructed circRNA-miRNA interaction networks through using bioinformatic tools [11,23]. However, it is not clear whether those circRNAs can function as ceRNA for the dysregulated miRNAs in ARDS.…”
Section: Discussionmentioning
confidence: 99%
“…Although the constituent ratio and mortality rate of NARDS in hospitalized newborns at the same time are low, the mortality rate of NARDS is more than 10%, so further study about NARDS is urgently needed (18). Now, existing studies have pointed out that circRNA plays a certain role in adult acute lung injury (ALI), traumatic lung injury (TLI), and lipopolysaccharide-induced acute lung injury rat model (19)(20)(21). At the same time, it has been suggested that miRNAs are involved in the pathogenesis of NARDS and play different roles in its pathological process (22).…”
Section: Discussionmentioning
confidence: 99%
“…Mounting studies have shown the evidence that circRNAs can function as miRNA sponge via ceRNA cross talk in various biologic processes, such as cancer, in ammation-related, or autoimmune diseases [7,8] . We and other studies have previously documented the differential expressed circRNAs in ARDS mice and constructed circRNA-miRNA interaction networks through using bioinformatics tools [13,25] . However, it is not clear whether those circRNAs can function as ceRNA for the dysregulated miRNAs in ARDS.…”
Section: Discussionmentioning
confidence: 99%